Identidades em transformação: efeitos de intercâmbios internacionais na formação docente - Emilioreli, Giovanna Maria (2017)
Interacting with teachers immersed in a multicultural environment is a way of sharing experiences and unveiling common issues in becoming a teacher, which may interfere in the identity of the additional language teacher. This qualitative study and socio-historical approach focused on nodal and causal moments that are characterized as outstanding in the language teacher training course, specifically considering professionals with experience in other countries. The exploratory-descriptive objectives were divided into a general objective -to recognize identity transformations and the resulting effects of the exchange experience. And the specific objectives – to analyze my own experience; a nalyze the other ex-exchange teachers‟experience; reflect on identity transformations as exchanges effect. These objectives were drawn according to two guiding questions, first one - What are the international exchanges effects that may have influenced the participants to become English language teachers? And the second - What are the main identity transformations arising from the exchange according to the perceptions of these participants? The main concepts that theoretically support the research are: Applied Linguistics ( KLEIMAN, 1995; KUMARAVADIVELU, 2006; OLIVEIRA, 2009); In Autobiographic Narrative (MAGALHÃES, 2010; PAIVA, 2008; ROMERO, 2010), then we have the legend Identidade (BLOCK, 2017; HALL, 2005); and within the same subtitle Teaching Identity with (SOUZA, 2016; VASCONCELOS, 2004); Still in the sequence of the Identity of the Teaching of the Additional Language Professional (BLOCK, 2015; STEIN, 2013), and to end on Identity, the Identities under construction being immersed in another culture ( PLEWS, 2014), followed by Teacher Training (LIMA; PIMENTA, 2012; MELLO, 2010); and to wind up the theoretical framework we have the cultural context at the time of immersion in another country (WILKINSON, 1998). After the survey and study the theoretical concepts, the analysis material was collected by interview technique and elaboration of my autobiographical narrative. Subsequently, the corpus organization was carried out, which allowed me to perform the interpretative basis analysis. The results point to the positive effects that exchanges provide for the transformation and re-signification of the identity, both personal and professional, which can be perceived by the excerpts taken from the participants statements that specifically highlight: the exchange‟s influence to become teachers; professional experience; identification not only as a language teacher, but as a speaker of the language; motivation to teach; new teaching methodologies; thinking about different cultural models and to appropriate of new teaching methods; language improvement; and interaction with another culture. I hope that this research contributes to a better understanding of the identity transformations as well as the effects of international exchanges in the language teachers training. From this work, new researches can be carried out in the Applied Linguistics area.